APPLICATION THEORY ON QUEUE SERVICE SYSTEM OF THE BANK IN INDONESIA TELLER - Lia Koestiaty; Drs. Eko Hadiyanto, MM Drs. Eko Hadiyanto, MM (Jurnal Sistem Informasi, 1997)
Combined model (M/M/1) and (M / M / S) customers will experience a hesitancy todetermine which queue should she entered, and also can cause queues on one teller sothat inefficient work time and the presence of other tellern . While using the modelsolutions are offered, namely the model (M / M / S) so customers can easily be servedand not confused determine the queue where they are going to live so that the numberof queues and customer waiting time can be reduced / minimized, and the efficiencyand effectiveness teller work can be controlled.